Kontekstualisasi cerita kreatif panji cindelaras bagi masyarakat Tulungagung - Halimatus Siti Khumairo; Sunu Catur Budiyono; Akhmad Qomaru Zaman (PPPM STKIP PGRI Lamongan, 2022)
Panji's story is an anonymous literary work that was born as a reflection of its constituents against the ongoing feud between the kingdoms of Jenggala and Kediri. The Panji story can be used as writing to commemorate the story. This study aims to find out how the community version of the Cindelaras Panji story in Tulungagung Regency, East Java, find out the Omben Jago site, and Penampihan temple as a representation of the Cindelaras Panji story and find out the function of the Panji story. story. The theory used in this study is the New Historicism theory from Stephen Greenblatt. This research method uses a qualitative approach. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques use data observation, transcripts, and data corpus, to interpret, explain, and describe stories.The results of the research were found in the form of the Panji Cindelaras story of the Tulungagung community, the Tulungagung Regency version. Based on the Omben Jago Site and Penampihan Temple as a representation of the Panji Cindelaras Story, a picture is formed of the origin of the Omben Jago Site, the relationship between the Panji Laras Story and Penampihan Temple and the Omben Jago Site, as well as Lingga and Penampihan Temple. Yoni at Penampihan Temple and Omben Jago Site. Based on its function, the Cindelaras Panji story can be described that the Cindelaras Panji story has a function as the pride of the community, besides that the function of the story also has the function of the Omben Jago site which is divided into two, namely religion. function and also as a function of story contextualization.